Stop the Snobbery! Why You’re Wrong About Community Colleges and Don’t Even Know It - Kim Leeder (In the Library with the Lead Pipe, 2012)
Several weeks ago I attended my first community college commencement. Despite my staff status, I was pleased to be invited to sit among the faculty behind the stage. From this vantage point I was able to watch the ceremony and play a small role in it (faculty, please stand; faculty, please sit) while reflecting upon [...]